The Role Of Parents In Children's Education: Pedagogical Implications Of Q.S Al-Maidah 104 - Djafar, Hilman; Sofyan, Abu; Hasyim, Ruslan; Riadi, Akhmad; Khan, Taqi Ullah (LP2M IAIN kUDUS, 2024)
In the modern era, the role of parents in their children's education has become increasingly complex and multifaceted. Scholars have made various studies regarding aspects, methods, processes, and educational objectives based on verses in the Al-Qur'an holy book. However, no research has been found on the pedagogical implications of the Al-Qur'an Surah Al-Maidah verse 104 regarding the role of parents towards childhood education. This study aims to determine parents' role in children's education according to Islamic education and the pedagogical implications of Surah Al-Maidah verse 104. This research is library research. Primary data were taken from the interpretation by Buya Hamka, Ibnu Katsir, and Ismail Haqqi Al-Buruswi, and secondary took from relevant Islamic education articles. The researcher acts as an instrument in this study. Collected the data by inventorying relevant literature titles, selecting the reading, examining, and classifying the reading results. Data analysis was performed by processing, categorizing, interpreting, and concluding. The results of the study show that parents act as educators, mentors, and role models for their children. Furthermore, to educate with sharia, to set a good example uswah, to educate in avoiding taqlid, teaching with knowledge, and to reprimand and remind are found as the pedagogical implications of QS. Al-Maidah verse 104. However, The specific context of this study restricts its generalizability to only parents' roles, based on the opinions of interpreters. Furthermore, a more comprehensive study could have been conducted for another research that empirical testing of the pedagogical implication of QS Al-Maidah 104 by utilizing a wider range of sources with diverse interpretations, and bolstered by numerous literary works to capture a wider range of perspectives.